New evidence, old puzzles: technology shocks and labor market dynamics - Almut Balleer (Kiel Institute for the World Economy (IfW), 2009)
Can the standard search-and-matching labor market model replicate the business cycle fluctuations of the job finding rate and the unemployment rate? In the model, fluctuations are prominently driven by productivity shocks which are commonly interpreted as technology shocks. I estimate different types of technology shocks from structural VARs and reassess the empirical performance of the standard model based on second moments that are conditional on technology shocks. Most prominently, the model replicates the conditional volatility of job finding and unemployment, so that the Shimer critique does not apply. Instead the model lacks non-technological disturbances to replicate the overall sample volatility. In addition, positive technology shocks lead to a fall in job finding and an increase in unemployment thereby opposing the dynamics in the standard model similar to the hours puzzle in Galí (1999).
Keywords: E24; E32; O33; 330; Labor market dynamics; technology shocks; structural VAR; search and matching; business cycle; Konjunkturelle Arbeitslosigkeit; Technologie; Produktivität; Schock; Arbeitsmarkttheorie; Arbeitsuche; Matching; VAR-Modell; Schätzung; USA